Prevalence of direct antiglobulin test positive in whole blood donors: Study at a tertiary blood center Northern India - Jyoti Bharti; Archana Solanki; Ashutosh Singh; Mallika Agarwal; Tulika Chandra (Asian Journal of Transfusion Science)
BACKGROUND: The direct antiglobulin test (DAT) detects red blood cell (RBC) sensitivity to complement or IgG in vivo. The clinical disorders of hemolytic disease of the newborn, hemolytic transfusion reaction, and autoimmune and drug-induced hemolytic anemia are some examples of those that can cause in vivo coating of RBCs with antibodies or complement autoimmune hemolytic anemia (AIHA). Rarely, DAT is positive in nonimmune-mediated hemolytic anemias as well. Standard donor screening techniques do not require the DAT to be performed. AIMS AND OBJECTIVES: The aim of the study was to assess the prevalence of DAT positive in healthy blood donors at a tertiary blood center in North India. MATERIALS AND METHODS: This 2-year prospective observational study included whole blood donors from January 2020 to December 2022. A total of 152,564 healthy blood donors including 150,246 (98.5%) males and 2318 (1.5%) females were donated at the department of transfusion medicine. RESULTS: Of a total of 152,564 donors, 150,246 (98.5%) were male, and 2,318 (1.5%) were female. Among the male donors, 11 (0.007%) had a history of blood transfusion and 16 (0.011%) tested DAT positive. Among the female donors, 15 (0.647%) had a history of blood transfusion and none of them tested DAT positive. CONCLUSION: We observed low levels of DAT positivity in healthy blood donors. Such donors should be regularly monitored to check for any long-term development of malignancies or clinical or laboratory indications of hemolysis. DAT-positive blood units do not supply the recipient at risk, which may cause negative consequences.